ANALISIS PENGARUH KONTROL DIRI, GAYA HIDUP, PENDAPATAN, TEKNOLOGI DIGITAL DAN ALAT PEMBAYARAN TERHADAP LITERASI KEUANGAN PADA MASYARAKAT - Ananda Eka Agustina; Hwihanus Hwihanus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the influence of self-control, lifestyle, income, digital technology, and digital payment usage on financial literacy. Although digital payment adoption in Indonesia continues to grow, financial literacy levels remain relatively low, highlighting the need to understand the factors that shape it. A quantitative approach was applied through questionnaires distributed to active users of digital payment tools. The results show that self-control significantly affects financial literacy, emphasizing the importance of psychological factors in shaping financial behavior. Lifestyle and digital payment usage do not influence financial literacy, indicating that digital payment functions mainly as a practical transaction tool rather than a financial education medium. Income affects digital payment usage but does not influence financial literacy. Moreover, digital technology does not moderate the relationship between digital payment usage and financial literacy. These findings underscore the importance of behavior-oriented financial education to improve financial literacy in the digital era.